Bridging the Gap: Implementasi Aplikasi Portofolio OBE untuk Evaluasi Pembelajaran yang Lebih Efektif dan Efisien - Imam Ahmad Ashari; Retno Agus Setiawan; Arif Setia Sandi A.; Deny Nugroho Triwibowo; Anggit Wirasto; Iis Setiawan Mangkunegara; Sony Kartika Wibisono (Universitas Methodist Indonesia, 2026)
The implementation of the Outcome-Based Education (OBE) curriculum is often hindered by repetitive manual administration. This community service aims to facilitate digital transformation through SIMPOBE application assistance for 39 lecturers at Universitas Harapan Bangsa. The method involved a hands-on workshop covering assessment alignment, RPS standardization, and PPEPP-based raw score input. Evaluation results show the application successfully bridged the gap between curriculum data and evaluation reports. Efficiency significantly improved as the system automatically links assessment components to CPL/CPMK, eliminating redundant input. Most participants (scores 4 and 5) expressed readiness for independent implementation by April 2026. In conclusion, portfolio digitalization effectively reduces human error and administrative burdens, supporting accountable institutional academic quality enhancement.